Drying and rehydration kinetics of peeled and unpeeled green apple slices (Granny Smith cv). Issue 10 (3rd October 2022) - Riveros-Gomez, Mathias; Baldán, Yanina; Román, María Celia; Fabani, María Paula; Mazza, Germán; Rodríguez, Rosa
Abstract: In this work, the kinetics of drying and rehydration of green apple slices peeled and unpeeled (Granny Smith cv) were studied. The apple slices were dried at 50, 60, and 70 °C, and after that, rehydrated at ambient ( Ta ) and boiling temperature ( Tb ). The drying kinetics were adjusted with the Dincer and Dost model, giving a good fit. Effective diffusivity ( Deff ) and the convective mass transfer coefficient ( hm ) were also determined, both coefficients increase with drying temperature, being 1.25 × 10 −9 m 2 s −1 and 9.53 × 10 −7 m 2 s −1 the highest values obtained for the peeled apple slices respectively. Peleg and Weibull models were adjusted to the rehydration experimental data obtaining a good fit ( R 2 > 0.99). Deff values increase significantly with rehydration temperature but take similar values between peeled and unpeeled samples. Acidity, pH, moisture content, solid soluble content, and equivalent diameter were determined to compare the fresh apple slices with those after dehydration and the post-rehydration process. The apple slices rehydrated at boiling temperature better preserved the characteristics of fresh samples due to the short immersion times in water, no significant differences were observed between peeled and unpeeled apples. According to the results, it is convenient to dry the apple slices unpeeled at 70 °C and rehydrate them at Tb . Graphical Abstract: UF0001